Theory-driven design of cadmium mineralizing layered double hydroxides for environmental remediation † - Li, Z; Xu, N; Ren, J; Hao, H; Gao, R; Kong, X; Yan, H; Hua, X; Peng, Y; Ma, S; O'Hare, D; Zhao, Y (Royal Society of Chemistry, 2024)
The environmental concern posed by toxic heavy metal pollution in soil and water has grown. Ca-based layered double hydroxides (LDHs) have shown exceptional efficacy in eliminating heavy metal cations through the formation of super-stable mineralization structures (SSMS). Nevertheless, it is still unclear how the intricate coordination environment of Ca2+ in Ca-based LDH materials affects the mineralization performance, which hinders the development and application of Ca-based LDH materials as efficient mineralizers. Herein, we discover that, in comparison to a standard LDH, the mineralization efficiency for Cd2+ ions may be significantly enhanced in the pentacoordinated structure of defect-containing Ca-5-LDH utilizing both density functional theory (DFT) and ab initio molecular dynamics (AIMD) simulations. Furthermore, the calcination-reconstruction technique can be utilized to successfully produce pentacoordinated Ca-5-LDH. Subsequent investigations verified that Ca-5-LDH exhibited double the mineralization performance (421.5 mg g−1) in comparison to the corresponding pristine seven coordinated Ca-7OH/H2O-LDH (191.2 mg g−1). The coordination-relative mineralization mechanism of Ca-based LDH was confirmed by both theoretical calculations and experimental results. The understanding of LDH materials and their possible use in environmental remediation are advanced by this research.